Laser Welding of Zr41Ti14Cu12Ni10Be23 Bulk Metallic Glass: Experiment and Temperature Field Simulation1. Issue 5 (28th January 2013) - Chen, Biao; Shi, Tielin; Li, Mo; Zhang, Zhaobo; Zhu, Zhijing; Liao, Guanglan
Abstract We investigate laser bonding of Zr41Ti14Cu12Ni10Be23 bulk metallic glass (BMG) using experiments and finite element simulation. The specimen plates with 5 × 30 × 1.3 mm3 are welded together successfully and the welded joint maintains fully amorphous under the welding parameters of 1.3 kW and 7 m min−1. To examine in detail the thermal stability of the welded joint, we employ the SYSWELD software to simulate the distribution of temperature field and thermal cycle curves. The simulation results are consistent with the laser welding experiments, and there is no intersection point between the thermal cycle curves and time–temperature‐transformation diagram, indicating that the joint retains amorphous structure.